Exploration of Lipid Content in Sargassum binderi Algae from the North Coast of Manokwari West Papua - Stepanus, Jamius Bin; Kolibongso, Duaitd (Indonesian Journal of Chemical Science and Technology (IJCST), 2024)
The aim of this research is to determine the potential of biodiesel from the algae Sargassum binderi from the North Coast of Manokwari by determining the lipid components contained in the algae. Lipid extraction was carried out using the soxhletation method with n-hexane solvent. Lipid percentage was determined via GCMS analysis. The research results obtained 4 lipid components consisting of hexadecanoic acid (palmitic acid), 9,12-hexadecadienoic acid, 9-octadecenoic acid (Z) (oleic acid) and octadecanoic acid (stearic acid) with a percentage of 18.12%, 4.75%, 19.4% and 4.29% respectively. The total percentage of lipid components extracted was 46.56%, almost half of the total extract.